Analyze breaking palm oil dormancy through chemical processes using multivariate analysis of variance - Widya Reza; Vitri Aprilla Handayani; Eko Sulistyono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Palm oil is a dormant plant. The main cause of oil palm seed dormancy is the hard and thick seed coat or shell, inhibiting the effective absorption of water and gases. The presence of a seed coat barrier causes the germination process of oil palm seeds to be hampered. This study aims to determine the effect of chemical treatment on breaking palm oil dormancy by immersion in a solution of strong acids, namely H2SO4, KNO3, and HCl. This study used a completely random design (CRD) with three treatments, four observations, and five replications. The results of the following study were analyzed using MANOVA with the parameters observed were germination rate, germination rate, seedling height, and most extended root length. Based on the analysis results, it was found that immersion with a solution of a strong acid, namely H2SO4, KNO3, and HCl, had different effects on breaking palm oil dormancy. The highest average germination rate was through immersion with HCl, which produced an average of 65.24. The highest average germination was through immersion in H2SO4 with an average of 8.52. In contrast, the average seedling height and most extended root length were soaked in HCl with an average of 35.28, and 15, respectively. Based on the results obtained, the best chemical treatment for breaking palm oil dormancy is through soaking with HCl.